2006
DOI: 10.1002/rcm.2485
|View full text |Cite
|
Sign up to set email alerts
|

The characterisation of selected antidepressant drugs using electrospray ionisation with ion trap mass spectrometry and with quadrupole time‐of‐flight mass spectrometry and their determination by high‐performance liquid chromatography/electrospray ionisation tandem mass spectrometry

Abstract: The electrospray ionisation ion trap tandem mass spectrometry (ESI-MS(n)) of selected antidepressant drugs, i.e., citalopram, fluoxetine, mirtazapine, paroxetine, sertraline, and venlafaxine, has been investigated. Sequential product ion fragmentation experiments (MS(n)) have been performed in order to elucidate the degradation pathways for the [M+H](+) ions and their predominant product ions. These MS(n) experiments show certain characteristic fragmentations in that functional groups are generally cleaved fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 21 publications
3
35
2
Order By: Relevance
“…This was done to establish the optimal NCE value that would allow, through MS 2 spectra, to analyze the structural stability of the sample, as this parameter has been used to predict drug metabolites at given NCE values as recommended by the MS manufacturer (25 or 30%) [32,44]. The third experiment was also done by tandem-MS at a fixed NCE value of 30%, for subsequent MS n analysis of the main fragment generated on the previous MS n−1 fragmentation (n = 3, 4).…”
Section: Esi-ms N Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This was done to establish the optimal NCE value that would allow, through MS 2 spectra, to analyze the structural stability of the sample, as this parameter has been used to predict drug metabolites at given NCE values as recommended by the MS manufacturer (25 or 30%) [32,44]. The third experiment was also done by tandem-MS at a fixed NCE value of 30%, for subsequent MS n analysis of the main fragment generated on the previous MS n−1 fragmentation (n = 3, 4).…”
Section: Esi-ms N Analysismentioning
confidence: 99%
“…to time-of-flight mass spectrometry (ToF-MS) [31,32,35]. ESI-MS n studies of antimalarial compounds as bisthiazolium or quinolines can be found on reports by Nicolas et al [38] or Smyth et al and O'Donnell et al [34,39], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…12,38 The existence of VIII as an intermediate in the degradation of III has also been confirmed by using electrospray ionization mass spectrometry (ESI-MS). 11 In our quest for the possible dehydration product, the alkenes VIII and IX have been targeted as structures with chemical formula matching the experimentally observed signal (m/z 192). The most favorable pathway which precedes the formation of VIII and IX corresponds to the loss of water from carbon-centered radical cation 5.…”
Section: Dehydration Of 5 With Alkene Formationmentioning
confidence: 99%
“…According to other experimental studies, hydrolysis and dehydration of paroxetine can result in several products with a molecular mass of 191. 2,[11][12][13] Therefore, in addition to the photoproduct IV, additional structures V-XI (Scheme 1) which match the observed MS signal should be considered as possible degradation products of paroxetine.…”
Section: Introductionmentioning
confidence: 99%
“…Reported methods for the determination of fluoxetine are mainly based on high performance liquid chromatography [2][3][4][5][6][7][8][9] and Gas chromatography [10][11][12] . Spectrofluoremetric methods have also used by few researchers [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%